Laila al-Othman’s Novel Ṣamt al-farāshāt (Silence of the Butterflies): Women’s Silence and Taboo - Naamneh, Mahmuod; Jaber, Saleem Abu (Advances in Social Sciences Research Journal, 2017)
Not Available